The Use of a Goal-Oriented Evaluation Model on the Dhuha Prayer Habit Program at Elementary School 2 Gunung Puteri Bogor - Safitri, Desvyana Wahyu Eka; Maulana, Ahmad Riziq; Yani, Ahmad (YASIN, 2025)
The habituation of students as their character is still homework in educational institutions. Therefore, a certain learning model is needed in order to accustom positive things for school residents, one of which is the habituation of worship. This research aims to analyze the application of the Goal Oriented Evaluation Model to the Dhuha prayer habituation program at Elementary School (SD) Character 2 Gunung Puteri Bogor and identify the obstacles faced in the evaluation process. The research method used is a qualitative method with data collection techniques in the form of observation, interviews, and document studies. The research results show that the application of this model focuses on achieving program objectives, namely increasing student worship discipline through the habit of Dhuha prayer. The evaluation was carried out based on indicators of student involvement, discipline, and changes in daily religious behaviour. However, several obstacles were faced, such as low student discipline, limited implementation time, and lack of support from parents. The research results are expected to be a reference for schools in improving and developing similar programs in the future.